PROSES PRODUKSI DAN PEMASARAN KULINER KIMBAB UNTUK PENGGEMAR KPOP DAN K-DRAMA - Aulia Ifha Sabnur; Andi Ananta Regina Putri; Nurul Salsabila; Irma; Viska Angraeni; Fajrullah Sabri; Sapar (Jurnal Abditani, 2023)
Production and Marketing Process of Kimbab for K-Pop and K-Drama Fans. The purpose of the Student Creativity and Entrepreneurship Program (PKM-K) is to encourage students to become entrepreneurs in the traditional Korean cuisine business of Kimbab. The implementation method of this program includes input, process (production), output, and evaluation. The program's results consist of conducting market surveys to determine the market conditions, interviewing five female students in the environment of Muhammadiyah Palopo University, conducting feasibility studies on the business to be carried out, and finally selecting the ingredients and providing the venue, equipment, and infrastructure to support the production process. The production process involves making Kimbab starting from preparing ingredients and tools until the Kimbab is marketed. The output is the ready-to-consume culinary product of Kimbab marketed to consumers. The final step is evaluation, which is carried out when the production of Kimbab products is complete. This step reviews any shortcomings that make consumers uncomfortable with our products. The conclusion of the PKM-K program for the Production and Marketing Process of Kimbab for K-Pop and K-Drama Fans can provide skills to students to remain innovative and creative in developing the traditional Korean cuisine business of Kimbab, provide opportunities for students to practice entrepreneurship with a comprehensive understanding of entrepreneurship concepts, and build the spirit of students to continue in business.